International Tax Potential in the Digital Economy: A Study on MNE Tax Avoidance and the Strengthening of Indonesia’s Tax Regime - Wibisono, Masodah (Jurnal Kajian Akuntansi, Auditing dan Perpajakan, 2025)
International tax issues have become increasingly complex alongside the rising activities of multinational enterprises (MNEs), particularly within the digital economy. This study analyzes tax avoidance strategies employed by a simulated company, DIGIO FP Group, which exploits the “Double Irish” scheme, aggressive transfer pricing, and tax treaty abuse to shift profits to low-tax jurisdictions. Using a content analysis approach and fiscal adjustment simulation, the study finds that although DIGIO FP generates substantial revenue from users in Indonesia, its tax contribution remains minimal due to an operational structure that does not reflect actual economic substance. Additionally, practices such as treaty shopping and inconsistencies with the beneficial ownership principle indicate potential treaty abuse. The discovery of hidden funds through the AEOI system highlights the need to strengthen oversight of offshore assets. These findings underscore the importance of implementing the Global Minimum Tax regime (PMK 136/2024), enforcing the arm’s length principle in transfer pricing, and reforming the definition of Permanent Establishment (PE). This research offers policy recommendations to enhance Indonesia's tax system in facing the challenges of globalization and digitalization of the economy.